High‐performance thermoplastic polyureas via a non‐isocyanate route from urea and aliphatic diamines. Issue 28 (2nd May 2022) - Lin, Chenxi; Xie, Kangzhou; Tang, Donglin
Abstract: Polyureas (PUrs) with excellent properties have been applied widely in many fields. These days attention has been turned to non‐isocyanate routes for PUr preparation due to the toxicity and the high cost of isocyanates. Urea is a green chemcial which can be either from urine or from recycled carbon dioxide and ammonia. Here we introduce a urea‐based route to prepare PUrs, by melt polycondensation of urea and 1, 10‐diaminodecane (DA‐10) or/and 1, 6‐diaminohexane (DA‐6) without catalyst, solvent, and high pressure. It is difficult to synthesize such thermoplastic PUrs from diisocyanate without any solvent since the melting point of PUr is normally higher than 170°C at which isocyanate is able to react with urea group to form biuret. The thermoplastic PUrs obtained in this study exhibit excellent mechanical and thermal properties. Furthermore, the properties can be adjusted by changing the feed ratio of diamines (DA‐6/DA‐10). The compression‐molded PUrs show even better mechanical properties than ultra‐high molecular weight polyethylene (UHMWPE). The values of Young's modulus, strength at break and elongation at break are found to be 230–300 MPa, 40–60 MPa and 200%–400%, respectively (except for PUr‐6). Therefore, this facile, non‐isocyanate approach provides a viable alternative to the current industrial process for high‐performance PUrs. Abstract : Linear polyureas are successfully synthesized from urea and two bio‐based aliphatic diamines, with no catalyst, no solvent, and no diisocyanate. The properties of polyureas can be tuned by changing the ratio of feeding diamines. The obtained polyureas exhibit competitive thermal and mechanical properties to commercial engineering plastics, such as polyamide, ultrahigh‐molecular weight polyethylene, and so forth.